A healthy bond: relationship between dog ownership, physical activity levels, motivation, physical self-concept and well-being in adolescents - Xabier Gonzalez-Santamaria; Josu Solabarrieta Eizaguirre; Miguel Ángel Fuentes García; Erika Borrajo Mena (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: physical inactivity, especially among adolescents, is linked to serious health problems, with girls being particularly affected. Given the increasing prevalence of dog ownership, dog-assisted physical activity programs could offer new strategies to counteract this issue.